Is Consensus a Good Thing in Science? - Westrum, Ron (Journal of Scientific Exploration, 2015)
Henry Bauer’s well-written Essay Review (in this issue) on “climate change” brings to mind another attempt to close off debate and pronounce that “Yup, now we know for sure”: The Condon Report on UFOs of 1968 (Condon et al. 1969). This was an attempt, on the part of the U.S. Air Force, to discourage interest in UFOs, and to make the issue appear finally resolved. Carried out by the University of Colorado, the project, under the direction of Edward Condon, conducted a number of investigations of UFOs. The Air Force used the resulting report as evidence that UFO research was a waste of time. For five years after its publication, they mostly got away with it. A post-publication review by the National Academy of Sciences had endorsed the Report. The Air Force was able to close Project Bluebook, reporting was discouraged, and what reports were made within the Air Force stayed in highly classified channels. It was a well-orchestrated piece of flimflammery, and it certainly appeared to be good science, but it wasn’t good science (Sturrock 1999, Hall 2001). In spite of the lengthy text of the book, about a thousand pages, the Report managed to obscure rather than inform.